Media Role in Promoting Tourism of Luang Prabang Capital - LATTANANONGSY, sengthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study was exploratory in nature and aimed to examine the role of the media in promoting ecotourism in Luang Prabang. A questionnaire was used as a data collection tool, with a sample of 685 tourists, and the data was analyzed using SPSS. The results showed that the media plays a significant role in promoting Tourism of Luang Prabang Capital. Most tourists were aware of information about tourist destinations in Luang Prabang Capital through digital media channels, such as YouTube ( =5.00, S.D = 0.00), followed by Facebook ( =4.70, S.D = 0.18), and TikTok ( =4.30, S.D = 0.26). Television media ( =3.64, S.D = 0.25), followed by billboard media ( = 3.61, S.D = 0.27), newspapers ( = 3.52, S.D = 0.38), radio broadcasting ( = 3.00, S.D = 0.74), and brochures distributed to tourists ( = 2.98, S.D = 1.02). Additionally, most tourists suggested that documentary media for various tourist destinations be created to be more diverse and modern ( = 4.27, S.D = 0.92). The presentation of tourist destinations through images was also considered important for promoting tourism, with a mean value of 4.24 and a standard deviation value of 0.98.